A Comparative Study of Friction Self-Piercing Riveting and Self-Piercing Riveting of Aluminum Alloy AA5182-O. (December 2021) - Ma, Yunwu; Shan, He; Niu, Sizhe; Li, Yongbing; Lin, Zhongqin; Ma, Ninshu
Abstract: In this paper, self-piercing riveting (SPR) and friction self-piercing riveting (F-SPR) processes were employed to join aluminum alloy AA5182-O sheets. Parallel studies were carried out to compare the two processes in terms of joint macrogeometry, tooling force, microhardness, quasi-static mechanical performance, and fatigue behavior. The results indicate that the F-SPR process formed both rivet–sheet interlocking and sheet–sheet solid-state bonding, whereas the SPR process only contained rivet–sheet interlocking. For the same rivet flaring, the F-SPR process required 63% less tooling force than the SPR process because of the softening effect of frictional heat and the lower rivet hardness of F-SPR. The decrease in the switch depth of the F-SPR resulted in more hardening of the aluminum alloy surrounding the rivet. The higher hardness of aluminum and formation of solid-state bonding enhanced the F-SPR joint stiffness under lap-shear loading, which contributed to the higher quasi-static lap-shear strength and longer fatigue life compared to those of the SPR joints.